LITERATURE REVIEW ON THE ROLE OF LEARNING INTERESTS ON LEARNING OUTCOMES OF ELEMENTARY AND HIGH SCHOOL STUDENTS - Utami, Riska; Fariza, Jihan; Alrefi, Alrefi (Program Studi Bimbingan dan Konseling FKIP UNJA, 2025)
This study aims to analyze the effect of learning interest on student learning outcomes at the elementary and high school levels through a systematic literature review. The research method uses a literature study by analyzing 20 journal articles published in the last 5 years. The results show that interest in learning has a significant effect on improving student learning outcomes in various subjects, with the level of influence varying from 11.6% to 85.74%. The determinants of interest in learning include internal (motivation, aspirations) and external aspects (teaching methods, parental support, school environment). The findings recommend an interest-based learning approach to improve education quality.